FAILURE ANALYSIS OF REINFORCED CONCRETE CROSSARMS IN OVERHEAD DISTRIBUTION LINES: A CASE STUDY - Reis, Elger Dias; Laizo, Aysser Saliba Monteiro; Dias Reis, Elvys (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2023)
Given that most electric power distribution in Brazil relies on overhead transmission lines, any disruption in the power supply can have significant societal implications. This paper provides a qualitative assessment of material creep, which can result in sudden breakage of transmission line structures. A specific case study is presented, focusing on the rupture of a reinforced concrete crossarm in União dos Palmares, Alagoas, Brazil, which belongs to Equatorial Energia’s distribution line. The crossarm failure led to a complete power outage in the entire city. This instance emphasizes the importance of further research on creep in concrete structures, particularly those utilized in transmission lines.